Effect of Trade Liberalization on Tax Revenue of East Africa Community Member Countries - Mutegi, Lewis; Okiro, Kennedy; Kisimbii, Johnbosco (European Journal of Business and Strategic Management, 2025)
Purpose: This study sought to examine the effect of trade liberalization on tax revenue of East Africa community member countries. Methodology: The study used descriptive research design and collected secondary data from 6 east Africa community member countries for the period between 2000 and 2023. The data was analyzed by use of simple linear regression analysis. Findings: The study revealed that trade liberalization has a statistically positive relationship with tax revenue of east Africa community member countries. Unique Contribution to Theory, Practice and Policy: This study contributes to validation of Hecksher-Ohlin (H-O) model in supporting the need for countries to embrace trade liberalization as a developmental strategy for developing nations to benefit from global integration, skills transfer, knowledge transfer and productive capabilities from developed nations. The study also contributes to development of optimal tax policy and trading policies with a view of enabling developing countries to maximize their potential on tax revenue for funding their development programs while at the same time remaining globally competitive to be able to attract foreign direct investments. This study also contributes to knowledge advancement by providing a framework for understanding how developing countries can achieve global economic integration by embracing trade liberalization and its impacts on the overall tax revenue processes of countries within a given trading bloc such as EAC.